(untitled) (Journal of Human Sciences, 2025)
At the present time, the community’s dependence on technology of all kinds has increased until it has become a necessity of the times, especially compared to its active role in various areas of life, as it opened a wide field for embodying the concept of the electronic village referred to by Marshall McLuhan. With the end of the twentieth century and the beginning of the third millennium, and through the possibility of interconnection And creating a cohesive fabric of computer networks, the Internet appeared to cover the entire globe, so there was a need to conduct a study on the effects of modern communication technology, especially social networks, on the Libyan family, and did the Libyan family actually benefit from the prospects and applications provided by modern communication technology? Research Importance:- The importance of this study lies in the following: the increase in social networking sites on the Internet and the ease of subscribing to them free of charge (free of charge) and the permanent technological development of the Internet, specifically social networks via the Internet (Facebook - Twitter - YouTube) and the increasing participation of adolescents and youth To social networks via the Internet as a way to highlight their personalities without restrictions or controls. The nature of the data: The research sample was selected using a random sample method, where the research sample consisted of ((82)) male and female employees from the Faculty of Literature in Sebha. The study relied on (the survey sheet, the personal interview questionnaire form) as a method for collecting data in this study to monitor the opinions, behaviors, and patterns of practice of Libyan family members in using Social networks, due to its suitability to the type of study, its methodological procedures, and its objective. The form included several elements, including knowledge of the extent of the respondent’s use of the Internet, the extent of the respondent’s use of social networks, and the extent of the impact of social networking sites on the user’s family or social relations. The most important results "1" The results showed that the sample’s use of social networks such as (Facebook - Twitter - YouTube) was for the purpose of exchanging information at a rate of (50.0%), and this may be due to the social, economic and political conditions that the individual lives within his society, while we find that (14.0%) of them prefer Communication networks because they are convenient and easy to access due to the social, economic and political conditions that the individual lives within his community. 2- The search results showed that the highest percentage was for individuals who use social networking sites because of (following up on the most important events and news) at a rate of (84.0%), compared to (26.0%) for individuals who use social networking sites because of (electronic marketing of some products and services) . 3- It is clear that the percentage of respondents who believed that social networking sites have a negative impact on their family relationships because it reduces family visits was (46.0%), compared to the lowest percentage (16.0%) for individuals who believed that social networking sites had a negative impact on their family relationships because .It publishes ideas that are inappropriate with the traditions and customs of the Libyan family.